Deciphering the morphological, molecular, and pathogenic variability in Fusarium species associated with potato dry rot disease - Pooja,; Chauhan, Prashant; Tiwari, Rahul Kumar; Saini, Anil Kumar; Kumar, Ankit; Rithesh, Lellapalli (Frontiers in Microbiology, 2025)
Potato (Solanum tuberosum L.), a member of the Solanaceae family, is a staple crop with vital importance for global food security. Various biotic and abiotic stresses affect potato crops in the field as well as in post-harvest conditions. Among biotic stresses, Fusarium dry rot, caused by the Fusarium species complex, is considered a major threat to potato cultivation. Fusarium is one of the most serious pathogens that causes dry rot in potatoes, resulting in huge yield losses. In addition, the pathogen variability depends on the ecogeographical region of potato cultivation. Therefore, to investigate the diversity, pathogenicity, and ecological variability of Fusarium species associated with dry rot in potatoes, 55 dry rot samples of potatoes infected with Fusarium spp. were collected, and from these samples, 53 Fusarium isolates were retrieved and characterized through micromorphological and molecular methods. The studies revealed that the isolated Fusarium spp. from the samples belonged to three species, namely Fusarium sambucinum, F. oxysporum, and F. solani. Among the collected species, F. sambucinum was the most dominant species with a high percentage of occurrence frequency. Furthermore, the pathogenicity tests of each isolate were conducted through the tuber inoculation method. The study revealed that out of all isolates, F. sambucinum was highly pathogenic to the susceptible potato cultivar Kufri Pukhraj. This study highlights the predominance and pathogenicity of Fusarium sambucinum among Fusarium species causing dry rot in potatoes, providing critical insights for developing targeted management strategies to mitigate yield losses and enhance potato crop resilience.